A review of the hirticeps-group of Fannia Robineau-Desvoidy (Diptera: Fanniidae), with the description of one new species from China - Wang, Ming-Fu; Wang, Rong-Rong (Zootaxa, 2006)
The Fannia hirticeps-group, an endemic Holarctic group, is reviewed to include Fannia xuei sp. nov. from China (Guizhou). The F. hirticeps-group is redefined and a key is given to the twelve known world species. Fannia limbata (Tiensuu) is transferred to this group, and new data on distributions are reported for the included species.